Emperor Ashoka, the Chief Patron of Buddhism: A Review - Kiron, Md. Ashikuzzaman Khan (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: The role of Emperor Ashoka is the main reason behind the position Buddhism has reached in the present world. He is one of the patrons of Buddhism. It was under his auspices that the third Buddhist council was held that Buddhism was able to establish itself in the position it has in the world today. Objective: The purpose of this study is to present a holistic assessment of how Emperor Ashoka was able to reach the present position by patronizing Buddhism. The article is presented in total three phases. Namely: To present a brief introduction to Emperor Ashoka; To assess and present the context of Emperor Ashoka's closeness with Buddhism; To evaluate Emperor Ashoka's contribution to Buddhism Methodology: This research employs a library-based analytical approach with a through review and critical analysis of associated historical texts and scholarly articles. The study explores the life and contributions of Emperor Ashoka, focusing on his patronage of Buddhism and its healthy impact on the global society. Result: Biography of Emperor Ashoka, his closeness and expansion of Buddhism has been explored in the article. Emperor Ashoka has been found to be able to reach the present position by patronizing Buddhism through the study. Conclusion: The Tripiṭaka was perfected by the third Buddhist council. He played an important role in propagating Buddhism in nine countries at that time, so this religion stands on a strong foundation in the world today. His son Mahendra and daughter Sanghamitra were among the Buddhist monks and nuns sent by Emperor Ashoka to the nine countries. Due to that continuity, the spread of Buddhism has been hindered in the world till today. The next successors are carrying on its continuity. As a result, a strong foundation of Buddhism is created.